Legal Protection For Bank Customers In The Use Of E-Kyc In Opening New Accounts Online As A Form Of Digital Financial Innovation (Study At The Jakarta Head Office Of The State Savings Bank) - Hutabarat, Jenrico Louis; Sunarmi, Sunarmi; Sukarja, Detania; Andriati, Syarifah Lisa (Jurnal Hukum Replik, 2024)
This research examines the function of E-KYC in Indonesian banking, the responsibility of banks to protect customers' personal data, and the form of data protection at BTN Jakarta Head Office, using analytical descriptive normative legal methods with a statutory approach. POJK Number 23/POJK.01/2019 allows customer verification through electronic means to replace direct meetings, where E-KYC is implemented as Customer Due Diligence which includes electronic identification, verification, and monitoring. The E-KYC organizing bank is required to meet the aspects of security, interconnectivity, system compatibility, technical support, and guarantee of service sustainability to be registered as a PSE, with sanctions from warnings to license revocation if negligent, as has been applied by BTN Mobile, which is registered as a domestic private PSE with international standard security technology to bridge the principle of knowing the customer and the right to privacy.